Growth of stunted elver of the Indonesian shortfin eel Anguilla bicolor McClelland, 1844 rearing in semi-natural media - Latifa Fekri; Ridwan Affandi; M. F. Rahardjo; Tatag Budiardi; Charles P. H. Simanjuntak (Jurnal Iktiologi Indonesia, 2019)
This study aimed to evaluate the growth of stunted elver Anguilla bicolor from three different periods of stunting process. Prior to experiment, the stunting process of elver was carried out by limiting the feeding rate at 2% of the fish biomass and temperature media with 24 oC for 2, 4, and 6 months period. The study used a completely randomized design with three different sources of stunted elvers (i.e., A = 2 months; B = 4 months; C = 6 months) as treatments with three replications. Measurement of RNA:DNA ratio, protein content, profile blood description and elver otolith growth was carried out at the beginning and end of rearing process. Post-stunting elvers were reared on artificial media designed according to elver habitat and controlled. Elver was stocked with 15 individuals in the artificial semi-natural media with a temperature of 28 oC and fed with 1 kg media-1 day-1 tubifex worm for three months. The results showed that the compensatory growth of stunted elvers increased two to three times with 100% of survival rate after three months of rearing process. Stunting has a significant effect on treatment B, indicated by the value of weight specific growth rates, RNA : DNA ratio, protein content, blood glucose levels and otolith growth of elvers. This study revealed that the growth performance of stunted elver reared in semi-natural media for four months is better than other treatments. Abstrak Penelitian ini bertujuan untuk mengevaluasi pertumbuhan elver Anguilla bicolor pascapembantutan dari tiga periode pembantutan yang berbeda. Proses pembantutan yang dilakukan sebelumnya dengan membatasi jumlah pemberian pakan sebanyak 2% dari biomassa dan pengaturan suhu media pemeliharaan 24 oC selama 2, 4, dan 6 bulan. Peneli-tian ini menggunakan rancangan acak lengkap dengan tiga perlakuan masa pembantutan yang berbeda (yaitu A = 2 bulan; B = 4 bulan; C = 6 bulan) dan masing-masing tiga ulangan. Pengukuran nisbah RNA:DNA, kandungan protein, gambaran profil darah dan pertumbuhan otolit elver dilakukan pada awal dan akhir pemeliharaan. Elver pascapembantutan dipelihara pada media buatan yang dirancang sesuai dengan habitat alami elver dan terkontrol. Elver ditebar 15 ekor per sekat pada media buatan semi alami dengan suhu 28 oC dan diberi pakan sebanyak 1 kg cacing sutera per media per hari selama tiga bulan pemeliharaan. Hasil penelitian menunjukkan bahwa pertumbuhan kompensasi elver pascapembantutan meningkat dua hingga tiga kali dengan sintasan 100% setelah pemeliharaan tiga bulan. Pembantutan memberikan pengaruh yang signifikan pada perlakuan B, ditunjukkan oleh nilai laju pertumbuh-an spesifik bobot, nisbah RNA:DNA, kandungan protein, kadar glukosa darah dan pertumbuhan otolit. Penelitian ini menunjukkan bahwa keragaan pertumbuhan elver pascapembantutan empat bulan yang dipelihara di media semi alami lebih baik daripada perlakuan lainnya.